PENGARUH PEMBERIAN JUS BUAH TOMAT (LYCOPERSICON ESCULENTUM MILL.) TERHADAP PEMBERSIHAN STAIN EKSTRINSIK PADA RESIN KOMPOSIT - Ibrahim, Kartika; Kawengian, Shirley E. S.; Gunawan, Paulina N. (e-GiGi, 2015)
Abstract: Discoloration of the composite resin is an aesthetic problem that often occurs primarily in anterior teeth caused by extrinsic and intrinsic factors. Bleaching is a kind of treatment that can improve the problem of composite discoloration. One of the bleaching materials oftenly used in dentistry is H2O2. H2O2 compound contained in tomatoes can be used as an alternative treatment to cope with the composite discoloration. This study aimed to determine the effect of tomato juice as extrinsic stain cleaner of the composite resin. This was a laboratory experimental study with a pre and post control group design. Samples were 20 resin composites molded in 5mm diameter and 2mm thickness. Samples were soaked in coffee solution for 10 days to get the extrinsic stain and then discoloration was measured with a spectrophotometer discoloration Libra S12 UV / Visible Biochrom. After that, samples were divided into 2 groups: the control group, immersed in mineral water; and the treatment group, immersed in tomato juice for 3 days. After immersion, measurements were done again with a spectrophotometer. The results were tested statistically using the Wilcoxon test with a P value < 0.05. Conclusion: Tomato juice was a significant extrinsic stain cleaner of the composite resin.Keywords: tomato juice, extrinsic stain, resin compositesAbstrak: Perubahan warna tumpatan komposit merupakan masalah estetik yang sering terjadi terutama pada gigi anterior yang disebabkan oleh faktor ekstrinsik dan intrinsik. Salah satu perawatan untuk menangani masalah ini ialah bleaching dengan H2O2. Senyawa H2O2 terkandung dalam buah tomat yang dapat digunakan sebagai perawatan alternatif untuk mengatasi perubahan warna komposit. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian jus buah tomat terhadap pembersihan stain ekstrinsik pada resin komposit. Jenis penelitian ini ialah eksperimental laboratorium dengan desain pre and post control group. Jumlah sampel penelitian 20 resin komposit yang dibentuk dengan diameter 5mm dan tebal 2mm. Sampel direndam dalam larutan kopi selama 10 hari untuk melihat adanya stain ekstrinsik kemudian dilakukan pengukuran perubahan warna dengan spektrofotometer Libra S12 UV/Visible BIOCHROM. Setelah itu sampel dibagi menjadi 2 kelompok, yaitu kelompok kontrol direndam dalam air mineral dan kelompok perlakuan di dalam jus buah tomat selama 3 hari. Setelah perendaman dilakukan pengukuran kembali dengan spektrofotometer. Hasil penelitian diuji secara statistik dengan uji Wilcoxon mendapatkan nilai P < 0,05. Simpulan: Jus buah tomat berpengaruh secara bermakna terhadap pembersihan stain ekstrinsik pada resin komposit.Kata kunci: jus buah tomat, stain ekstrinsik, resin komposit